Long-term clinical performance and complications of zirconia-based tooth- and implant-supported fixed prosthodontic restorations: A summary of systematic reviews. (August 2021) - Laumbacher, Harald; Strasser, Thomas; Knüttel, Helge; Rosentritt, Martin
Abstract: Objectives: To present an overview on systematic reviews on prosthodontic zirconia restorations and to discuss long-term complications as well as information on anatomical and functional changes to the masticatory system. Data/Sources: MEDLINE, EMBASE, Trip medical, and Cochrane Library databases were searched for systematic reviews up to February 2021. Bias was assessed and clinical survival and complications were analyzed. Study selection: 38 eligible articles published between 2006 and 2021 were included. The reviews were based on 128 in vivo studies on approximately 10, 000 zirconia restorations. 5-year cumulative survival rates varied between 91.2% and 95.9% for tooth-supported (TS) single crowns (SC), 89.4% and 100% for TS multi-unit fixed dental prostheses (FDP), 97.1% and 97.6% for implant-supported (IS) SCs and 93.0% and 100% for IS FDPs. Chipping was the most often technical complication, followed by framework fracture, loss of retention, marginal discrepancies/discoloration, occlusal roughness and abutment/screw loosening. Color mismatch was the only esthetic complication. Biological complications were caries, endodontic complications, tooth fracture, periodontal disease, abrasion/attrition, persisting pain, high sensitivity, peri‑implantitis and soft tissue issues. Patients with bruxism were only examined sporadically. Conclusions: 5-year results for zirconia restorations were satisfactory. The predominant technical problem of veneering fractures could be overcome with adapted design or fabrication and application of monolithic restorations, but reviews of clinical studies on this subject are rare. The impact of zirconia restorations on the masticatory system remains unclear. Clinical significance: Zirconia restorations are experiencing a rapidly increasing use in dental practice. Being highly wear-resistant, hard and durable, it can be assumed that they do not follow natural abrasion and changes in the masticatory system. Possible long-term effects on the stomatognathic system as a whole should therefore be considered.